Determining The Company Debt Threshold In Order To Determine Bankruptcy Status - suyikati (Fakultas Hukum Universitas Widya Mataram, 2023)
The Indonesian Bankruptcy Law has not been based on a philosophy that should be in accordance with the principles of the Bankruptcy Principle itself, where the philosophy of the Bankruptcy Law has not been able to explain debtors who have debts greater than their assets. The application of this principle should ideally be a condition for the debtor to be declared bankrupt, where if the debtor is insolvent (the debtor's assets are less than its debts), it is not enough if the debtor stops or fails to pay its debts. If the debtor's assets exceed its debts, then the settlement of the debt and credit should be done through an ordinary civil lawsuit. The application of bankruptcy regulations according to Article 2 of the Bankruptcy Law should not only be based on three aspects, which include the existence of debt, at least two (two) creditors, due time, and collectibles, but also the application of a minimum threshold of capital and assets owned so that the company can be monitored to see if it will be able to rise with the assets and capital it has. Keywords: threshold, company, bankruptcy